ANTIBACTERIAL of ETHANOL EXTRACT (Muntingia calabura L.) AGAINST Streptococcus agalactiae as CAUSE SUBCLINICAL MASTITIS in DAIRY COWS - Imro’atul Khasanah; Sarwiyono Sarwiyono; Puguh Surjowardojo (TERNAK TROPIKA Journal of Tropical Animal Production, 2014)
A research on the antibacterial ability of ethanol extract (Muntingia calabura L.) and its concentration effect on bacteria Streptococcus agalactiae growth was investigated in this experiment. Several tests were conducted by the inhibition of diffusion Kirby-Bauer method using a Completely Randomized Design with 6 treatments and 4 replication. Ethanol extract concentrations were varied into 10%, 20%, 30%, 40% and water extract 20% and Iodips 10% (as control). The research showed that ethanol extract (Muntingia calabura L.) had ability to hinder significantly the growth of Streptococcus agalactiae bacteria (P<0.05). The highest action was found on 40% concentration, namely 7,01 mm and the lowest action was on water extract 20% concentration namely 6,00 mm. Higher concentration of the ethanol extract Muntingia calabura leaves also increased its ability to hinder the growth of Streptococcus agalactiae. It can be concluded that the increasing concentration of ethanol extract Muntingia calabura leaf showed high inhibition diameter of Streptococcus agalactiae. It can be suggested that ethanol extract of Muntingia calabura L. can be used by farmers to prevent mastitis.   Keywords : Inhibition ability, Streptococcus agalactiae, ethanol extract, Muntingia calabura